A FROM FOREIGNER TO NATURALIZATION, A RECENT DISTRIBUTION RECORDS OF TAWNY COSTER ACRAEA TERPSICORE (LEPIDOPTERA: NYMPHALIDAE) IN SUMATRA - Iqbal, Muhammad; Aprilia, Ina; Setiawan, Arum; Setiawan, Doni; Yustian, Indra (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2020)
The Tawny coster Acraea terpsicore (Lepidoptera: Nymphalidae) is a non-native species of butterfly that has been recorded in Sumatra since 2009. Summarize recent review confirmed 40 spatial distribution records of A. terpsicore between 2009 to 2020. These records suggest A. terpsicore have widely distributed and colonialized in Sumatra.